Sustainable Growth Rate, Capital Structure, Dividend Policy And Share Price Performance: The Case Of Malaysian Public-Listed Shariah-Compliant Firms - Norfhadzilahwati Rahim
The sustainable growth rate is a growth rate for a company to achieve by maintaining target capital structure, target dividend policy, and its operating performance. The interdependency between financial and operating policy is an important decision to be considered in order to sustain the growth rate and improve share price performance. In relation to financial policy, the Securities Commission has introduced new screening methodology benchmarks based on financial ratios to be listed as Shariah-compliant firms in 2013. Due to this new screening methodology benchmarks, the reduction number of Shariah-compliant firms making only 653 firms in November 2013 out of the total 801 firms in May 2013 from the total listed securities on Bursa Malaysia. One of the reasons for the reduction in the number of Shariah-compliant firms is due to higher conventional debt, where the debt ratios are more than the limit or threshold of 33 per cent. Driven by this fact, this study investigates (1) the existence of a target capital structure and target dividend policy; (2) the mediating effect of sustainable growth rate on the relationship between firm specific factors (capital structure, dividend policy, profitability, company efficiency and firm size) and share price performance; and (3) whether there is a capital structure threshold in the relationship between capital structure and the sustainable growth rate. In this study, 181 public-listed Shariah-compliant securities in Malaysia were selected from 2007 until 2016. Data were collected from the Thomson Reuters database. This study employed panel data analysis, i.e. Pooled OLS, Random Effect Model, Fixed Effect Model, Generalized Method of Moment, Structural Equation Model (SEM), and Static Panel Threshold regression using Stata software. The findings of objective one indicate that target capital structure and target dividend policy exists for Shariah-compliant firms. The results of objective two conclude that the sustainable growth rate is one of the important factors influencing share price performance and that it also plays a role as mediator variable. The evidence indicates a strong relationship between capital structure, dividend policy, profitability and firm size on the sustainable growth rate. The third objective shows that the capital structure threshold is not limited to 33 percent (total debt to total assets), but to 37 percent to sustain the growth. In order to remain listed as Shariah-compliant companies, the choice is to take Shariah securities or Islamic debt after hitting 33 percent. In addition, the sustainable growth rate is important for helping firms to manage and control their operating and financial strategies. The findings of this study can be used as a reference for future studies that examine other aspects of the sustainable growth rate.